(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
The measures taken in Israel against the spread of the pandemic seem difficult to implement and the long-standing religious and social problems affecting Israeli society appear to have worsen in the last months. Although some social control actions appear to be effective, the Jewish fear extremist religious groups withdraw political support from the Government did not allow a strict application of the rules, while the Arab minority, that is about to celebrate the ritual fast, will have to deal with a real curfew. However, it seems that the crisis generated by the virus is leading political forces, that have been polarized for about a year, to form a government of national unity.